Patterns and characteristics of polypharmacy among elderly residents in Danish nursing homes - Jacob Astorp; Mimoza Gjela; Pernille Jensen; Rasmus D Bak; Parisa Gazerani (Future Science OA)
Aim: To identify patterns and characteristics of polypharmacy among elderly residents in Danish nursing homes in the Northern region of Denmark. Materials & methods: Twenty-five nursing homes were contacted, where each supplied 20 randomly selected anonymized residents’ information. Residents were 65 years or older, concurrently taking five or more medications. Drug–drug interactions and potential adverse effects were investigated. Results: One hundred residents (68% females; 32% males) were included. The most prevalent co-morbid condition was cardiovascular disease, and the most prevalent medications were for gastrointestinal- and metabolism-related conditions. Age influenced the number of drugs (p = 0.013) and drug–drug interactions per resident (p = 0.039), with a positive correlation. Conclusion: Elderly residents of the studied nursing homes were potentially affected by an inappropriate polypharmacy.